2016
DOI: 10.15690/pf.v13i4.1605
|View full text |Cite
|
Sign up to set email alerts
|

The Efficiency of Adalimumab in Cases of Chronic Methotrexate-Resistant Juvenile Idiopathic Arthritis-Associated Anterior Uveitis: Retrospective Case Series Study

Abstract: Background: Juvenile idiopathic arthritis (JIA) associated uveitis may be the cause of not only visual acuity decrement, but also blindness. At the same time, in some patients therapy with methotrexate can not prevent the development of these complications.Objective: Our aim was to investigate the efficiency and safety of using a tumor necrosis factor inhibitor (adalimumab) in patients with JIA-associated uveitis.Methods: We conducted a retrospective single-arm study of a series of cases. The results of using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…Moreover, Mazzawi et al [91] explored the effects of FMT on symptoms and duodenal enteroendocrine cells in IBS patients and reported the effectiveness of FMT in treating IBS-D patients, revealing that IBS symptom scores for abdominal pain ( P = 0.005), diarrhea ( P = 0.004), and anorexia ( P = 0.096); IBS severity scores ( P = 0.0002); and Bristol Stool Scale scores ( P = 0.02) were significantly decreased after FMT treatment for 3 weeks. Gaidar et al [92] investigated the effectiveness of colonoscopy-assisted FMT in treating refractory IBS-D, IBS-C, and IBS-M patients. They reported that 75% of patients experienced relief from abdominal pain ( P < 0.01) and that stool frequency and consistency in all IBS-M and IBS-D patients returned to normal.…”
Section: Clinical Efficacy Of Fmt In Treating Ibsmentioning
confidence: 99%
“…Moreover, Mazzawi et al [91] explored the effects of FMT on symptoms and duodenal enteroendocrine cells in IBS patients and reported the effectiveness of FMT in treating IBS-D patients, revealing that IBS symptom scores for abdominal pain ( P = 0.005), diarrhea ( P = 0.004), and anorexia ( P = 0.096); IBS severity scores ( P = 0.0002); and Bristol Stool Scale scores ( P = 0.02) were significantly decreased after FMT treatment for 3 weeks. Gaidar et al [92] investigated the effectiveness of colonoscopy-assisted FMT in treating refractory IBS-D, IBS-C, and IBS-M patients. They reported that 75% of patients experienced relief from abdominal pain ( P < 0.01) and that stool frequency and consistency in all IBS-M and IBS-D patients returned to normal.…”
Section: Clinical Efficacy Of Fmt In Treating Ibsmentioning
confidence: 99%
“…РОССИЙСКИЙ ВЕСТНИК ПЕРИНАТОЛОГИИ И ПЕДИАТРИИ, 2019; 64: (2) ROSSIYSKIY VESTNIK PERINATOLOGII I PEDIATRII, 2019; 64: (2) купировать лишь в 2 (из 22) глазах [34]. Ретроспективный анализ историй болезни 36 пациентов продемонстрировал снижение частоты обострений с 4 до 0 на одного больного в год [35]. В проспективном открытом нерандомизированном исследовании при применении комбинированной терапии метотрексатом и адалимумабом у 27 детей с увеитом, ассоциированным с ювенильным идиопатическим артритом, отмечался выраженное положительное влияние как на суставной синдром, так и на орган зрения [9].…”
Section: обзоры литературыunclassified